"Basically it's the Usual Whole Teen Girl Thing": Stage‐of‐Life Categories on a Children and Young People's Helpline. Issue 1 (21st July 2017) - Cromdal, Jakob; Danby, Susan; Emmison, Michael; Osvaldsson, Karin; Cobb‐Moore, Charlotte
Abstract : This article explores the practices of membership categorization in the interactions of clients and counselors on a national Australian helpline (Kids Helpline [KHL]) for children and young persons. Our focus is on membership categories drawn from three membership category devices (MCDs): stage‐of‐life (SOL), age, and family. Analysis draws on data across different contact modalities—email and web‐counseling sessions—to examine how category‐generated features are relevantly occasioned, attended to, and managed by the parties in the course of interaction. This shows clients' use of MCDs in presenting their trouble and building a relevant case for their grievance. By examining counselors' subsequent receipts of the clients' complaints, we are able to trace some of the cultural knowledge that the clients' categorizations make relevant to the counselors. Moreover, the analysis demonstrates how the inherent flexibility of MCDs allows counselors to exploit these same categorial resources and to re‐specify the clients' trouble in a more positive fashion to accomplish counseling work. In explicating how taken‐for‐granted notions of the lifespan as well as of family relations are mobilized by participants in KHL's sessions, the findings contribute to previous studies of social interaction in counseling, and to research on social identity and categorization more broadly.